การศึกษาความต้องการพัฒนาธุรกิจชุมชนในเขตบางเขน - โพธิ์มณี เกรียงไกร; พรหมฤาษี สุภาภรณ์ (Phranakhon Rajabhat Research Journal : Humanities and Social Sciences, 2015)
การวิจัยเรื่องการศึกษาความต้องการพัฒนาธุรกิจชุมชนในเขตบางเขน มีวัตถุประสงค์เพื่อศึกษารูปแบบทางการตลาด ความต้องการของผู้ประกอบการ และความ ต้องการในการพัฒนาธุรกิจชุมชนของผู้ประกอบธุรกิจชุมชนในเขตบางเขน เป็นการวิจัย เชิงคุณภาพด้วยการสัมภาษณ์แบบเจาะลึก โดยการสัมภาษณ์เจ้าของธุรกิจชุมชนที่ขึ้น ทะเบียนกับเขตบางเขน จำนวน 39 คน ผลการวิจัยธุรกิจชุมชนในเขตบางเขนพบว่า รูปแบบทางการตลาดของธุรกิจชุมชน มีปัจจัยทางการตลาดสามารถอธิบายได้ 4 ปัจจัยคือ ด้านผลิตภัณฑ์มีการผลิตเป็น ครอบครัวสืบต่อกันมาทั้งในส่วนของบรรจุภัณฑ์ คุณภาพ วัตถุดิบการผลิต ชื่อตราสินค้ามี การผลิตออกมาจากความต้องการเสนอขายมากกว่าตอบสนองความต้องการของผู้ซื้อ ด้านของราคาผู้ประกอบการธุรกิจชุมชนจะมีรูปแบบของการคิดราคาขายจากการดูที่ต้นทุน การผลิตเป็นหลัก ด้านช่องทางการจัดจำหน่ายเป็นลักษณะจากผู้ผลิตถึงผู้บริโภคโดยตรง ส่วนด้านการส่งเสริมการตลาดจะเป็นด้านที่ธุรกิจชุมชนให้ความสำคัญน้อยที่สุดเนื่องจากให้ ความเห็นว่าสิ้นเปลืองค่าใช้จ่ายผู้ซื้อผลิตภัณฑ์ส่วนมากจะได้มาจากผู้ที่ซื้อประจำหรือมีการ บอกต่อแนะนำกันมาอยู่แล้ว ความต้องการของผู้ประกอบการซึ่งเป็นความต้องการในการพัฒนาตนเองแบ่ง ออกเป็นด้านกระบวนการผลิต แรงงาน เครื่องมือ วัตถุดิบ เงินทุน ประสบการณ์ ความรู้ ด้านความทันสมัยของผลิตภัณฑ์ รูปร่าง สีสันของผลิตภัณฑ์ เอกลักษณ์ และความโดดเด่น การขายผลิตภัณฑ์ ด้านคุณภาพของผลิตภัณฑ์ ด้านมาตรฐานการผลิต ด้านบรรจุภัณฑ์ ด้านฉลาก หรือตราผลิตภัณฑ์ การขนส่งผลิตภัณฑ์ และด้านชื่อเสียงของผลิตภัณฑ์ ความต้องการในการพัฒนาธุรกิจชุมชนซึ่งเป็นผู้ประกอบการร้องขอความช่วยใน ด้านดังต่อไปนี้ การช่วยเหลือจากรัฐ เงินสนับสนุนจากรัฐ การฝึกอบรม หรือ การช่วยเหลือด้านความรู้จากหน่วยงานต่างๆ การจัดหาแหล่งเงินกู้ ด้านเศรษฐกิจ ด้านความร่วมมือจากชุมชน ความเป็นผลิตภัณฑ์เอกลักษณ์ของจังหวัด ด้านการแข่งขัน ด้านการจัดหาสถานที่จำหน่าย และด้านการประชาสัมพันธ์ของรัฐ THE STUDY OF NEED FOR THE DEVELOPMENT OF COMMUNITY BUSINESS ENTERPRISES IN BANGKHEN DISTRICT The purposes of the study were to investigate 1) the marketing patterns, 2) the entrepreneurs’ needs, and 3) the needs in the development of community business enterprises of the community business entrepreneurs in Bangkhen district. The samples were 39 licensed entrepreneurs. The instrument was an in-depth interview. The qualitative method was employed in this study. The results were as follows: The marketing patterns of community business enterprises could be explained based on 4 factors. as for the product factor, there was a succession of family production for packaging, quality, materials, brand, Supplies were more than demands of the customers. For the pricing factor, the community business entrepreneurs set the price of the products according to their production cost. as, for the distribution channel factor, there was a direct delivery of products from a producer to customer. Finally, for marketing promotion factor, the community business entrepreneurs paid the least attention to this factor they considhed it a waste of money and many customers bought their products by word of mouth. the entrepreneurs were demonstrated needs for self development which were producing process (workforce, tools, materials, capital, work experiences, knowledge), trend (shape, color, identity, standpoint, product selling), product quality, production standard, packaging, labeling or branding, product distribution, and product fame. The needs in the development of community business enterprises of the community business entrepreneurs were the government supports, government financial support, training, knowledge support from organizations, loan services, economy, community cooperation, provincial product identity, competitiveness, distribution channel, and governmental public relations.